Exploring the Role of Socio-Economic Factors in Maintaining Biodiversity in Protected Biosphere Reserve - Nurwarinda, Henry; Adelabu, Samuel Adewale; Ramoelo, Abel; Mashiane, Katlego; Durowoju, Olufemi Sunday; Jackson, Colbert Mutiso (Department of Geography Education, University of Jember, Indonesia, 2025)
Socio-economic factors and conservation of biodiversity interplay is very important but understudied especially in the biosphere reserves. This paper evaluates the contribution of socio-economic factors in sustaining biodiversity in Vhembe Biosphere Reserve, which is abundant in biological diversity and heritage. The study employs the mixed-methods strategy in which the quantitative method is applied using the data provided by the Statistics South Africa (SSA) census on education, employment, and income level to determine the relationship between this data and the concept of biodiversity conservation. The factors are identified as major contributors to biodiversity destruction in the region. The data on loss of biodiversity were obtained through SSA and analysed using R-Studio with multiple logistic regression. The model that best fit was the level of education, the lowest AIC was 66.33, which indicates that the level of education is a significant contributor to the degradation of biodiversity. It is worth noting that the education levels of “No schooling”, “Some primary” and “Some secondary” had a great impact on the biodiversity variable. “No schooling” was the most significant negative variable that influenced the loss of biodiversity. The research highlighted how environmental education and awareness can be utilised to conserve natural resources. The solution to these socio-economic driving factors would contribute to achieving a sustainable equilibrium between human development and the ecological conservation of the Vhembe Biosphere Reserve. The study will help in comprehending the effects of socio-economics on biodiversity and offer practical implications to policymakers and conservationists around the world.